Seed Germination and Seedling Growth in some Selected Fast Growing Fuelwood Plants - Sinhababu, A.; Banerjee, A.; Kar, R. K. (Indian Forester, 2007)
Seed germination and seedling growth were studied in seven fast growing fuelwood yielding leguminous trees, viz. Acacia auriculiformis, Acacia holosericea, Albizia lebbek, Bauhinia variegata, Cassia fistula, Cassia siamea and Leucaena leucocephala. To improve the low germination rate, seeds of these species were either incubated in light (in 8 h daily cycle) or pretreated with hot water (80Â°C for 5 minutes) or with phytohormones (IAA and GA) and nitrogenous substances (potassium nitrate and thiourea). Significant increase in germination percentage over control was observed in all species with hot water pretreatment. Light alone could not improve germination; however, it became effective in seeds pretreated with hot water. Pretreatment with hormone and nitrogenous substances also showed limited improvement in germination in some cases. Seedling growth was comparatively high in B. variegata and A. lebbek, which may be correlated with higher seed weight in these species.